1999
DOI: 10.1128/mcb.19.11.7428
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Modulation of Replication Activity ofSaccharomyces cerevisiaeAutonomously Replicating Sequences by Transcription Factors

Abstract: Evidence for transcription factor involvement in the initiation of DNA replication at certain replication origins in Saccharomyces cerevisiae mainly comes from an indirect assay which measures the mitotic stability of plasmids containing an autonomously replicating sequence (ARS), a selectable marker gene, and a centromere. In order to eliminate the effect of transcription factor binding to the selectable marker gene or centromere in such assays, we have adapted the DpnI assay to directly measure ARS replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Transcribed sequences are generally replicated earlier in S phase in the cells where they are expressed than in cells where they are not (22,76), possibly as a result of the modification of chromatin structure by transcription factors (48). However, several investigators report positive (11,19,21,25,34,36,47,53,66,86) or negative (11,43,53) effects of transcription factors on DNA replication, either directly through the binding of replication proteins or indirectly via modulation of chromatin structure. Alternatively, it has been suggested that cells may replicate active sequences prior to gene expression as a mechanism to avoid disruption of pre-RCs by the passage of the transcriptional machinery (12,28,57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcribed sequences are generally replicated earlier in S phase in the cells where they are expressed than in cells where they are not (22,76), possibly as a result of the modification of chromatin structure by transcription factors (48). However, several investigators report positive (11,19,21,25,34,36,47,53,66,86) or negative (11,43,53) effects of transcription factors on DNA replication, either directly through the binding of replication proteins or indirectly via modulation of chromatin structure. Alternatively, it has been suggested that cells may replicate active sequences prior to gene expression as a mechanism to avoid disruption of pre-RCs by the passage of the transcriptional machinery (12,28,57).…”
mentioning
confidence: 99%
“…Transcribed sequences are generally replicated earlier in S phase in the cells where they are expressed than in cells where they are not (22,76), possibly as a result of the modification of chromatin structure by transcription factors (48). However, several investigators report positive (11,19,21,25,34,36,47,53,66,86) or negative (11,43,53) …”
mentioning
confidence: 99%
“…Viral transcription factors have been shown to directly recruit replication factors, such as the polyomavirus recruiting the viral large T antigen replication initiator complex with the AP1 transcription factor (Murakami et al 1991; Ito et al 1996) and the Epstein–Barr virus recruiting cellular ORC with the EBNA1 transcription factor (Chaudhuri et al 2001; Dhar et al 2001 Schepers et al 2001; Ritzi et al 2003). Many origins in Saccharomyces cerevisiae (autonomously replicating sequences, ARS) contain binding sites for transcription factors (Li et al 1998; Hu et al 1999; Kohzaki et al 1999) including the B3 element of ARS1 which enhances ARS activity and is bound by the transcription factor, Abf1 (Mahrahrens and Stillman 1992). Interestingly, both the S-phase promoting transcription factor complex, E2F-Rb (Royzman et al 1999; Bosco et al 2001; Cayirlioglu et al 2001, 2003) and the Myb transcription factor complex (Beall et al 2002; Beall et al 2004) have been implicated in regulating DNA amplification loci in Drosophila follicle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, initiation occurs at multiple sites within replication zones that are defined by their chromosomal contexts rather than nucleotide sequences (29,46). Indeed, the activity of replication origins is responsive to their contexts (9,36). It has been shown that replication origins taken out of their native environment are no longer temporally regulated (35,52) and that silent replication origins are no longer repressed (23).…”
mentioning
confidence: 99%